Real-time traffic signal control for intersections based on dynamic O–D estimation and multi-objective optimisation: combined model and algorithm - Jiao, Pengpeng; Sun, Tuo; Li, Dongyue; Guo, Han; Li, Ruimin; Hou, Zenghao (IET intelligent transport systems, 2018)
Detectors are challenged in providing stable and accurate information of the dynamic origin–destination (O–D) flows for real-time adaptive traffic signal timing operation. However, the dynamic O–D estimation technique is capable of providing a short-term turn-flow data for the signal-timing adjustment. Meanwhile, the real-time signal timing variations will affect the dynamic O–D flows in an actual network. Therefore, the dynamic O–D estimation and the real-time signal control closely interact with each. A combined model is proposed to dynamically calculate the signal adjustment answering the variation of the real-time O–D flows by minimising the accumulative queues in entering approaches. A case study was conducted to validate the proposed model and algorithms, and the result showed the traffic efficiency of the case study intersection was improved.